HARAPAN DAN KENYATAAN DALAM BERKARIR DI KANTOR AKUNTAN PUBLIK: SUATU PERBANDINGAN ANTARA MAHASISWA AKUNTANSI DAN AUDITOR - DEASY ARIYANTI RAHAYUNINGSIH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
During the last few years, many researches in the job satisfaction of career in public accounting firms have been done. The previous research has shownn that there was a significant difference between auditor's perception and accounting student's perception on career in public accounting firms. Those differences based on job duties and responsibility, advancement, tarining and supervision (promotion and career advancement) and personal concern. The purpose of current study is to investigate whether there is a significant difference between auditors' perception and accounting students' perception on career in public accounting firms based on job duties and responsibility, advancement, training and supervision, personality concern and financial remuneration. This research adds financial remuneration which include salary, compensation, allowances and bonus as a variable that was not used ini the previous research. Results from statistical analysis indicate that there is no difference between auditors' perception and accounting students' perception based on job duties and responsibility in public accounting firms and there are significant differences between auditor's perception and accounting students' perception based on advancement, training and supervision, personality concern and financial remuneration in public accounting firms.